소아청소년에서 명상의 임상적 적용 - 곽영숙(Young Sook Kwack), 문덕수(Duk-Soo Moon) (Singyŏng chŏngsin ŭihak, 2020)
Meditation is one of the psychological therapeutic techniques that can be applied to many conditions, including stress reduction. Meditation can be an alternative to overcoming the limitations of existing therapies, including medication. In particular, this can be helpful for children who have limitations in using medication due to brain development and limitations of psychotherapy, which is done mainly by language. Previous studies have shown that mindfulness meditation helped enhance attention, increase the coping ability, reduce stress, and reduce depression and anxiety in children and adolescents, but there is insufficient evidence to use it as a primary treatment. A larger number of well-controlled studies will be needed to obtain an evidence base for expanding clinical application. KCI Citation Count: 2